2023
DOI: 10.1002/lsm.23715
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time laser speckle contrast imaging measurement during normothermic machine perfusion in pretransplant kidney assessment

Yitian Fang,
Lisanne van Ooijen,
Gisela Ambagtsheer
et al.

Abstract: ObjectivesNormothermic machine perfusion (NMP) provides a platform for pre‐transplant kidney quality assessment that is essential for the use of marginal donor kidneys. Laser speckle contrast imaging (LSCI) presents distinct advantages as a real‐time and noncontact imaging technique for measuring microcirculation. In this study, we aimed to assess the value of LSCI in visualizing renal cortical perfusion and investigate the additional value of dual‐side LSCI measurements compared to single aspect measurement d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Furthermore, Fang et al. demonstrated that dual‐side LSCI‐monitoring could be valuable for descriptive perfusion assessment during NMP 14 . By introducing the microembolization model during LSCI monitoring of rcBFI, we demonstrated that besides visually detection of perfusion in the outer renal cortex, it is possible to find a relationship between LSCI signal and changes in renal cortex perfusion.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Furthermore, Fang et al. demonstrated that dual‐side LSCI‐monitoring could be valuable for descriptive perfusion assessment during NMP 14 . By introducing the microembolization model during LSCI monitoring of rcBFI, we demonstrated that besides visually detection of perfusion in the outer renal cortex, it is possible to find a relationship between LSCI signal and changes in renal cortex perfusion.…”
Section: Discussionmentioning
confidence: 80%
“…In comparison, Fang et al. found a clear correlation between the slow increase in pump‐delivered total renal blood flow in a pressure controlled NMP system and the corresponding LSCI‐measured changes in renal cortex microperfusion during the first hour of reperfusion 14 . Indicating a correlation between the total delivered renal blood flow and LSCI‐measured changes in renal cortex microperfusion.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation